GROWTH PARAMETERS AND FORAGE YIELD OF TWO GRAIN SORGHUM (Sorghum bicolor L. Moench) VARIETIES UNDER DIFFERENT PLANTING DATES AND AGES OF HARVEST IN SHIKA - Munza, Bello M.; Hassan, M. R.; Tanko, R. J.; Yashim, S. M.; Abashi, T. J.; Sulim, P. Y.; Alkali, G. Z. (FUDMA JOURNAL OF SCIENCES, 2021)
To determine the influence of sorghum variety, planting dates and ages of harvest on growth parameters and forage yield of grain sorghum (Sorghum bicolor L. Moench) in Shika, Nigeria, an experiment was conducted in split plots in the National Animal Production Research Institute, Shika, Nigeria. The experimental treatments comprised of two sorghum varieties (SAMSORG-16 as V1 and SAMSORG-17 as V2), three planting dates (15th June, 30th June and 14th July as P1, P2 and P3) and three ages of harvest (6, 10 and 14 weeks after sowing as C1, C2 and C3), respectively. Results showed that plant height of sorghum bicolor significantly (P
Keywords: Age of harvest, sorghum, variety and planting date